2019
DOI: 10.1063/1.5079906
|View full text |Cite
|
Sign up to set email alerts
|

Full particle-in-cell simulation of the interaction between two plasmas for laboratory experiments on the generation of magnetized collisionless shocks with high-power lasers

Abstract: A preliminary numerical experiment is conducted for laboratory experiments on the generation of magnetized collisionless shocks with high-power lasers by using one-dimensional particle-in-cell simulation. The present study deals with the interaction between a moving Aluminum plasma and a Nitrogen plasma at rest. In the numerical experiment, the Nitrogen plasma is unmagnetized or magnetized by a weak external magnetic field. Since the previous study suggested the generation of spontaneous magnetic field in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Previous experiments have revealed that even in the unmagnetized case, selfgenerated magnetic field (i.e., Biermann field) is crucial in the ion reflection [26], which plays an important role in the formation of perpendicular shocks. This is also indicated by one-dimensional (1D) PIC simulation [27].…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Previous experiments have revealed that even in the unmagnetized case, selfgenerated magnetic field (i.e., Biermann field) is crucial in the ion reflection [26], which plays an important role in the formation of perpendicular shocks. This is also indicated by one-dimensional (1D) PIC simulation [27].…”
Section: Introductionmentioning
confidence: 61%
“…We recorded the scattered light of ion feature with an intensified charge-couple device (ICCD) with 3 ns exposure time. In this paper, we discuss the role of self-generated field (via Biermann battery effect) in Al plasma [27]. Unfortunately, there was no direct measurement of magnetic fields in this experiment to conclusively indicate that the Biermann field is playing an important role.…”
Section: Methodsmentioning
confidence: 95%
“…Shock formation and particle acceleration have previously been studied for various astrophysical and laboratory conditions in many PIC simulations [8][9][10]31,[33][34][35][36][37]. They do not, however, fully reproduce our experimental conditions for which the expanding shell plasma carrying selfgenerated magnetic field interacts with a fast-moving plasma jet.…”
Section: -2mentioning
confidence: 90%
“…2(b)]. We attribute the source of the upstream magnetic fields in zone III to be the Biermann battery effect [30,31]. Hydrodynamic simulations indicate that such fields are generated in the expanding shell plasma.…”
Section: -2mentioning
confidence: 99%
“…More typical values for the latter fall in the ∼2-4 range for recent simulations (Umeda et al, 2014;Matsukiyo and Matsumoto, 2015;Zeković, 2019). However, much larger values have been used in cases where one can reduce the simulation to one spatial dimension (Umeda et al, 2019). Despite all of the progress made since the early full PIC simulations, there still remains two striking discrepancies between observations and many simulations: the amplitude and wavelength at which the strongest electric fields are observed and inconsistencies in the thickness of the shock ramp.…”
Section: Kinetic Simulationsmentioning
confidence: 99%